Cyberbullying Body-Shaming Levels in Adolescence - Collantes, Leonel Hernandez; Saputra, Fajar Ananda; Solikhah, Putri Riadatus; Laksana, Trisna Chandra; Yakti, Novan Kuncoro; Tipagau, Jecksoniel (Association for Scientific Computing Electrical and Engineering, 2022)
Social media is a medium that teenagers very often use. Interaction media that users can use to easily interact, share, and social network without limits. The development of this social media can cause many impacts. This media will also have a harmful impact if used excessively. These problems arise in individuals who use the internet excessively, such as playing online games outside the limits of teaching to cause behavioral changes such as rudeness and aggression. Besides that, problems in the cyber world are commonly called cyberbullying. In addition, social media users easily express and publish their emotions and thoughts, including negative thoughts and emotions for others. The impact of this is the occurrence of bullying on social media. Cyberbullying, or cyberbullying, is a negotiation act that occurs and uses cyber media. Bullying often occurs through insults, threats, and humiliation on social media and text messages. The form of insult in cyberbullying is by bullying someone's physical appearance or better known as body shaming. Body shaming is a form of verbalemotional violence often not realized by the perpetrator because it is generally considered normal. Someone doing body shaming varies, from lighting the atmosphere, having fun, and inviting laughter to have reasons meant to insult